Assess the Impact of Corporate Governance on Corporate Performance - HUANG, SUNG-HSIANG (2009)
The purpose of this study is to examine the impact of corporate governance on corporate performance. This study uses a panel data form analysis covering a period 2004-2008 of 240 FTSE 350 public limited companies. The Combined code of best practice demands companies would have to release the information of corporate governance in annual financial reporting as the required condition for going public. In the sample of 240 FTSE 350 public limited companies, the statistical results find an economically important and statistical association between corporate governance and Tobin’s Q. The findings show that corporate governance has the significant (negative and positive) association with corporate performance of British public limited companies and the findings are consistent with preceding studies of Coughlan and Schmidt 1985, Wesibach 1988, Warner et al., 2006, and Lick, Netter and Yang (2006).